Solar-microbial hybrid device based on oxygen-deficient niobium pentoxide anodes for sustainable hydrogen production. Issue 12 (2nd October 2015) - Li, Mingyang; He, Xinjun; Zeng, Yinxiang; Chen, Meiqiong; Zhang, Ziyang; Yang, Hao; Fang, Pingping; Lu, Xihong; Tong, Yexiang
Abstract : A new solar-microbial hybrid device based on oxygen-deficient Nb2 O5 anodes for sustainable hydrogen generation without external bias was demonstrated. Abstract : Hydrogen gas is emerging as an attractive fuel with high energy density for the direction of energy resources in the future. Designing integrated devices based on a photoelectrochemical (PEC) cell and a microbial fuel cell (MFC) represents a promising strategy to produce hydrogen fuel at a low price. In this work, we demonstrate a new solar-microbial (PEC–MFC) hybrid device based on the oxygen-deficient Nb2 O5 nanoporous (Nb2 O5− x NPs) anodes for sustainable hydrogen generation without external bias for the first time. Owing to the improved conductivity and porous structure, the as-prepared Nb2 O5− x NPs film yields a remarkable photocurrent density of 0.9 mA cm −2 at 0.6 V ( vs. SCE) in 1 M KOH aqueous solution under light irradiation, and can achieve a maximum power density of 1196 mW m −2 when used as an anode in a MFC device. More importantly, a solar-microbial hybrid system by combining a PEC cell with a MFC is designed, in which the Nb2 O5− x NPs electrodes function as both anodes. The as-fabricated PEC–MFC hybrid device can simultaneously realize electricity and hydrogen using organic matter and solar light at zero external bias. This novel design and attempt might provide guidance for other materials to convert and store energy.